Leadership Style As A Predictor Of Organizational Commitment Among Sports Personnel In South-East Sports Development Commission Of Nigeria - Ezeadim, Helen; ANANOMO, L.E ANANOMO (S&Co Publishing, 2025)
This study investigated leadership style as a predictor of organizational commitment among sports personnel in the South East Sports Development Commission. The research was guided by three research questions and tested three null hypotheses at a 0.05 level of significance. A correlational research design was adopted, with a population of 838 sports officials. A sample size of 271 was selected using the Taro Yamane formula and stratified random sampling technique. A structured questionnaire developed by the researcher was used for data collection. The instrument’s reliability was confirmed using the Cronbach Alpha method, yielding a reliability coefficient of 0.81 for the Leadership Style Questionnaire (LSQ) and 0.79 for the Organizational Commitment Questionnaire (OCQ). Data were analyzed using simple regression analysis. Findings revealed that transformational leadership style is a strong and significant predictor of organizational commitment. Transactional leadership style was also a significant, though moderate, predictor, while laissez-faire leadership style had the weakest predictive value, yet remained statistically significant. The study also showed that leadership styles are strong, positive, and significant correlates of organizational commitment among sports personnel in the South East Sports Development Commission. Based on these findings, the study recommended that sports administrators adopt more transformational and transactional leadership approaches. These styles are more likely to inspire and motivate personnel toward improved commitment and performance. In contrast, the laissez-faire leadership approach was discouraged due to its weak impact on organizational commitment.